BENTUK KOLABORASI GURU BIMBINGAN DAN KONSELING DENGAN GURU MATA PELAJARAN DALAM MENGATASI PERMASALAHAN PESERTA DIDIK - Novi Rosita Rahmawati (Universitas Islam Negeri Mataram, 2020)
This research is to observe the collaboration of guidance and counseling teacher with islamic education teacher in handling students’ problems. The subjects of this research were guidance and counseling teacher and islamic education teacher of SMAN 3 Kediri. The data was collected through interview, observation, and documentation. The data analysis was descriptive qualitative by three stages of data simplification, data presentation, and drawing conclusion. The collected data was then arranged and classified for drawing the conclusion. The results showed there were 4 problems of SMAN 3 Kediri students, among others: 1) dating excessively, (2) arriving late, (3) skipping school, and (4) not carrying out midday prayers in congregation. Guidance and Counseling Teachers with Islamic Religious Education teachers formally and informally. Preventive action is also taken by care to minimize the impact of these problems.